Development of hot surfaces generated by friction contacts of titanium alloy and steel. (September 2020) - Pan, He; Zhang, Yang
When light alloys used in coal mine, the sparks generated by mechanical friction and impacts are the main effective ignition source. While the hot surfaces are concomitant in friction process, prior to the occurrence of mechanical sparks, whether the hot surfaces will be an effective ignition source. Then this paper focuses on the development of hot surfaces generated by TC4 titanium alloy at the low friction velocities. Experiments and finite element simulation methods were used together to describe the temperature field of TC4 titanium alloy. It was found that the temperature of hot surfaces increased with the load and increased much faster at higher relative speed. By means of regression analysis, the variation law of friction coefficient and contact pressure with loads and the variation law of hot surface temperature with friction coefficient and pressure were studied, then the fitting curve of hot surface temperature was obtained. The results of calculations and experiments indicate that hot surfaces generated by light alloy was possible to be an effective ignition source for methane air mixture in coal mine.